Foresight for food markets: Developing and implementing market forecasting methods/models - Dorosh, Paul A.; Mustafa, Shoumi; Kabir, Razin; Shaima, Nabila Afrin (International Food Policy Research Institute, 2024)
The “Foresight for Food Markets: Developing and Implementing Market Forecasting Methods/Models with Hands-on Training at the FPMU” is an element of Integrated Food Policy Research Program (IFPRP). Originally signed in 2016 between the Government of Bangladesh (GoB) and the Joint Venture (JV) comprising the International Food Policy Research Institute (IFPRI), the Bangladesh Institute of the Development Studies (BIDS), and the University of Illinois, IFPRP was extended and modified in subsequent periods. The most recent updated contract between the GoB and the JV was signed in mid-2022. Deliverable 4.3, Foresight for Food Markets: Developing and Implementing Market Forecasting Methods/Models with Hands-on Training at the FPMU is one of the new deliverables included in the updated contract. Rising prices of essential commodities affect consumer welfare and pose a serious challenge to the Government of Bangladesh. Knowing prices of essentials in advance would allow the government to take necessary measures to restrain the extent of price increases or to mitigate effects of rising prices; such measures could include provisions of direct distributions of rice and wheat through social safety net programs or of subsidized open market sales on the one hand and engaging in direct imports of essentials or easing import restrictions for the private sector, on the other. Because price fluctuations are a feature of a free market, there is a persistent need for the government to be able to project consumer prices in advance. Accordingly, it is important that in addition to receiving estimates prepared by external experts, the government has the ability to obtain its own price projections; the government should have the estimates when it needs them and for commodities for which such information is needed. Against this backdrop, IFPRP is providing hands-on training on price projection techniques to officials from the Food Planning and Monitoring Unit (FPMU), the Directorate General of Food (DG Food), and the Ministry of Food (MoFood). It is envisioned that trained officials from the DG Food, the Ministry of Food, and mostly from the FPMU will produce price projection estimates on their own with IFPRP personnel helping a consultative capacity.